Laparoscopic management of hydatid cyst of liver - Pradhan, Sumita; Ghimire, Bikal; Kansakar, Prasan; Bhandar, rAMESH Singh; Lakhey, Paleshwan Joshi; Singh, YP; Vaidya, P; Mishra, P; Singh, KP (Journal of Society of Surgeons of Nepal, 2016)
Background and Objectives: The surgical treatment of liver hydatid disease has evolved dramatically and laparoscopic treatment has shown encouraging results with the advantages of minimally invasive surgery. We conducted this study to determine the outcome of laparoscopic management of hydatid disease of the liver.Methods: Consecutive patients with this disease reporting to our department from July 2014 to July 2015 were offered laparoscopic management. All patients received pre- and postoperative albendazole. The laparoscopic technique consisted of aspiration of the cyst fluid, sterilization, suction and drainage of the cavity, deroofing and addition of omentoplasty. Age, sex, duration of surgery, surgical morbidity, hospital stay and evidence of hydatid cyst recurrence were measured.Results: Twenty six patients had laparoscopic treatment for hepatic hydatid cysts. Females were 18 (69.2%) and males were 8 (30.8%). Mean age of patients was 37.46 ± 15.96 years (range 17-74 years). Pain was the commonest presentation occurring in 21 (80.8%).The right lobe of the liver was most commonly involved in 20 patients (76.9%). The mean cyst size was 6.77 cm (range, 5 cm to 12 cm). Minor spillage of cyst contents occurred in 5 patients (19.23%) and major spillage occurred in 1 patient (3.8%). The mean duration of surgery was 84.81 ± 28.93 minutes (range 50 – 150 minutes). Conversion was needed in 2 (7.7%). Complications included portsite infection in 2 (7.7%), bile leak in 3 (11.5 %), fever in 5 (19.2%) and chest infection in 2 (7.7%) cases. Mean hospital stay is 4.58 ± 3.40 days (range 3-16). There was no mortality in the series. The average follow-up period is 7.81 ± 2.57 months. There have been no recurrences to date however 1 patient was lost to follow up.Conclusion: Laparoscopic management of hydatid cysts of the liver is a safe and effective option with advantage of minimally invasive surgery in properly selected patients.